Mechanisms of normal reflection at metal interfaces studied by Andreev-reflection spectroscopy - Gloos, K.; Tuuli, E. (Физика низких температур, 2014)
Andreev-reflection spectroscopy of elemental superconductors in contact with nonmagnetic normal metals reveals that the strength of normal-reflection varies only slightly. This observation imposes strong constrictions on the three possible normal-reflection mechanisms: tunneling through a dielectric barrier, reflection due to the different electronic properties of the two electrodes, and diffusive transport caused by elastic scattering in the contact region. We discuss in detail the role played by Fermi-surface mismatch, represented by the different Fermi velocities on both sides of the contact interface. We find that it is at least not the dominant mechanism and possibly completely absent in the Andreev-reflection process.